Penentuan Material dan Ketebalan Kritis Isolator Pada Exhaust Pipe Generator Set 350 Kva - Candra Eka Wijayanto; Jejen Jaelani Frihatna; Wisnu Wijaya (LPPM Universitas Sangga Buana, 2025)
This study aims to determine experimentally the critical thickness and related material of insulator to minimize heat loss of the exhaust pipe in a diesel engine driving a 350 kVA power generator. The method used in this study is an experimental approach. The data collection technique is carried out by direct measurement of temperatures. The heat transfer rate test was carried out by coating the exhaust pipe using two insulator materials, namely insulator A and insulator B. Insulator A used fiberglass tape material which has a value of k = 0,038 W/m.°C. While insulator B uses ceramic fiber material with a value of k = 0,06 W/m.°C. This heat transfer rate data has been then calculated based on the measured data taken using a Fluke type 62 max+ thermometer that can measure temperatures from −30 °C to 650 °C (−22 °F to 1202 °F). The results of the study show that: (1) Insulator material B is more appropriate to minimize heat loss in the exhaust pipe of the diesel engine driving a 350 kVA power generator, with the data obtained that the heat flowing from inside to outside the cylinder at point 1 insulator B = 31,553 W is smaller compared to insulator A = 82,356 W, the heat flowing from inside to outside the cylinder at point 2 insulator B = 31,462 W is smaller compared to insulator A = 79,985 W. The heat lost with the addition of insulator B = 40,923 W is smaller than the insulator A = 89,874 W. (2) The critical thickness to minimize heat loss in the diesel engine driving a 350 KVA power generator is the minimum thickness of insulator material A = 4,75 mm, the minimum thickness of insulator material B = 7,5 mm.